Flying Fox Hemolytic Fever, Description of a New Zoonosis Caused by Candidatus Mycoplasma haemohominis. (29th October 2020) - Descloux, Elodie; Mediannikov, Oleg; Gourinat, Ann-Claire; Colot, Julien; Chauvet, Martine; Mermoud, Isabelle; Desoutter, Denise; Cazorla, Cécile; Klement-Frutos, Elise; Antonini, Luca; Levasseur, Anthony; Bossi, Vincent; et al.
Abstract: Background: Hemotropic mycoplasmas, previously classified in the genus Eperythrozoon, have been reported as causing human infections in Brazil, China, Japan, and Spain. Methods: In 2017, we detected DNA from Candidatus Mycoplasma haemohominis in the blood of a Melanesian patient from New Caledonia presenting with febrile splenomegaly, weight loss, life-threatening autoimmune hemolytic anemia, and hemophagocytosis. The full genome of the bacterium was sequenced from a blood isolate. Subsequently, we retrospectively (2011–2017) and prospectively (2018–2019) tested patients who had been hospitalized with a similar clinico-biological picture. In addition, as these patients had been in contact with frugivorous bats (authorized under conditions for hunting and eating in New Caledonia), we investigated the role of these animals and their biting flies by testing them for hemotropic mycoplasmas. Results: There were 15 patients found to be infected by this hemotropic mycoplasma. Among them, 4 (27%) died following splenectomy performed either for spontaneous spleen rupture or to cure refractory autoimmune hemolytic anemia. The bacterium was cultivated from the patient's blood. The full genome of the Neocaledonian Candidatus M. haemohominis strain differed from that of a recently identified Japanese strain. Of 40 tested Pteropus bats, 40% were positive; 100% of collected bat flies Cyclopodia horsfieldi (Nycteribiidae, Diptera) were positive. Human, bat, and dipteran strains were highly similar. Conclusions: The bacterium being widely distributed in bats, Candidatus M. haemohominis, should be regarded as a potential cause of severe infections in humans. Abstract : We report 15 cases of a new frugivorous bat-transmitted zoonosis caused by Candidatus Mycoplasma haemohominis in New Caledonia. Patients suffered from life-threatening autoimmune hemolytic anemia and hemophagocytosis. The lethality was 27%. The disease was cured with tetracyclines.